Impact of training on changes in perceived stress and cytokine production - Main, L. C.; Dawson, B.; Grove, J. R.; Landers, G. J.; Goodman, C. (Research in Sports Medicine, 2009)
Data on training of competitive athletes and the inflammatory response, and, more specifically, the utility of psychological inventories to monitor this response in regards to overreaching is limited. The aim of the present study was to investigate the association of the Perceived Stress Scale (PSS) and inflammatory markers in elite rowers. Eight rowers (males n = 4; females n = 4) were monitored over an 8-week training period, comprising 12 sessions each week and training an average 3.11 h·d-1. Training volume was periodized weekly while intensity was maintained throughout the study. Perceived stress was measured weekly pretraining, and capillary blood samples (500 µL) were taken post-training. Significant associations between perceived stress and cytokines interleukin-6 (p < .05) and tumor necrosis factor alpha (p < .05) were observed. While further investigation of the role of cytokines in the overtraining process is required, these data provide preliminary support for an association between perceived stress and the inflammatory responses to training.